CLIMATE EMERGENCY: A PROPOSAL FOR A SOCIO-PARTICIPATORY CONSERVATION UNIT FOR WATER RESTORATION IN THE PANTANAL - Vacchiano, Marcelo Caetano; Castrillon, Solange Kimie Ikeda; de Figueiredo, Daniela Maimoni; Xavier, Fernando Francisco; Daher, Felipe Rodrigues Gil; Lenzi, Ítalo Luiz Corrêa; de Freitas Silgueiro, Vinícius; Spanholi, Maira Luiza; da Silva Nunes, Josué Ribeiro; da Silva, Carolina Joana (Seven Editora, 2025)
The Pantanal, the largest continuous floodplain in the world, depends on the flood pulse to maintain its hydrological connectivity and biodiversity. Climate change affects the aquatic ecosystem, altering rainfall patterns and increasing the frequency of droughts, which impacts water availability and ecosystem services. The creation of conservation units (CUs) is proposed as an adaptation strategy to mitigate these impacts, particularly in sensitive areas such as the Chacororé–Sinhá Mariana Lake System, which suffered significant damage from the 2020 drought and extensive fires. The proposal to create a CU aims to protect water, biodiversity, and local culture, thereby ensuring the maintenance of the living conditions of traditional communities. The proposed area covers 63,990 hectares and includes several geomorphological units and soil types, with the flood pulse regulating ecological processes. Changes in land cover, such as the conversion of native vegetation into anthropogenic areas, represent a threat to the sustainability of the Pantanal. Creating the CU is seen as a way to promote the sustainable use of natural resources and ensure the resilience of the Pantanal in the face of the challenges imposed by climate change and human activities. The proposal is based on studies of the area’s physical, biotic, and socio-environmental aspects, aiming at the long-term protection of this important biome. DOI: https://doi.org/10.56238/sevened2025.029-061